2012
DOI: 10.2466/30.25.27.pms.115.5.581-593
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence-Anticipation Timing Requirements are Different in Racket Sports

Abstract: The aim of this study was to compare the coincidence-anticipation timing accuracy of athletes of different racket sports with various stimulus velocity requirements. Ninety players (15 girls, 15 boys for each sport) from tennis (M age = 12.4 yr., SD = 1.4), badminton (M age = 12.5 yr., SD = 1.4), and table tennis (M age = 12.4 yr., SD = 1.2) participated in this study. Three different stimulus velocities, low, moderate, and high, were used to simulate the velocity requirements of these racket sports. Tennis pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 26 publications
(26 reference statements)
0
50
0
6
Order By: Relevance
“…Moreover, the amount of feedback can affect learning a skill in different ways, in that frequent feedback has been found to enhance acquisition of the skill but less frequent feedback enhances retention of the skill (Akpinar, Popovic, & Kirazci, 2012). Learning a new task, especially the anticipation-timing task tested in this study, can also be affected by the level of sports participation of the individual (Akpinar, Devrilmez, & Kirazci, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, the amount of feedback can affect learning a skill in different ways, in that frequent feedback has been found to enhance acquisition of the skill but less frequent feedback enhances retention of the skill (Akpinar, Popovic, & Kirazci, 2012). Learning a new task, especially the anticipation-timing task tested in this study, can also be affected by the level of sports participation of the individual (Akpinar, Devrilmez, & Kirazci, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the control group may have developed through growth or daily experiences of visual motion perception. Thus, knowledge that contributes to extending farther the subjective vanishing location of a moving target is likely acquired as a function of experiences with increased movement velocity (Akpinar, Devrilmez, & Kirazci, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In a PM task, participants view a moving target that is subsequently occluded, and participants then respond when the moving target would arrive at a goal if the target continued moving even after it was occluded from the observer's sight. A number of studies using the PM task have revealed that experts have superior timing ability compared with novices (Akpinar, Devrilmez, & Kirazci, 2012;Ripoll & Latiri, 1997;Tenenbaum, Sar-El, & Bar-Eli, 2000) due to accurate estimation of the time-to-contact (TTC), which is one of the critical factors for correctly intercepting a moving object (Tresilian, 1995). DeLucia and Liddell (1998) reported that cognitive motion extrapolation for the future location of a moving target after it disappears is associated positively with TTC estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing popularity of this sport and according to previous studies (Lees, 2003;Akpinar, Devrilmez, & Kirazci, 2012) which assumed that the major racket sports are badminton, squash, table tennis and tennis, no consideration has been provided for padel. As consequence, research in padel practitioners is rather poor with respect to that of other similar racket sports such as tennis (Ferrauti, Bergeron, Pluim, & Weber, 2001;O´Donoghue & Ingram, 2001;Smekal et al, 2001), badminton (Cabello & González-Badillo, 2003;Faude et al, 2007, Ooi et al, 2009, and squash (Chin, Steininger, So, Clark, & Wong, 1995;Girard et al, 2007).…”
Section: Introductionmentioning
confidence: 99%